Indirect payments: when the Mental Capacity Act interacts with the personalisation agenda. (30th April 2015) - Jepson, Marcus; Laybourne, Anne; Williams, Val; Cyhlarova, Eva; Williamson, Toby; Robotham, Daniel
Abstract: This paper reports findings from a study that aimed to explore how practitioners were bringing together the demands of the personalisation agenda, in particular the offer of direct payments (DPs), with the Mental Capacity Act, and to investigate current practices of offering and administering indirect payments for people who lack capacity to consent to them, including the use of 'suitable person' proxies under the new regulations (DH, 2009). The study adopted a qualitative interview‐based design; participants were social work practitioners (67) and recipients of 'indirect' payments (18) in six local authorities in England in 2011–2012. The paper reports on five key decision‐making points in the indirect payments process: the decision to take on an indirect payment, the assessment of mental capacity, the identification of a suitable person, the establishment of the care recipient's best interests and the decisions about how to execute the indirect payment. We found that practitioners and suitable people had different experiences of the system, although in both cases, there was overarching support for the benefits of enabling people who lack capacity to consent to a DP to receive their social care funding in the form of an 'indirect' payment via a proxy suitable person.